Comparative immunogenicity assessment of biosimilar natalizumab to its reference medicine: a matching immunogenicity profile - Chamberlain, Paul; Hemmer, Bernhard; Höfler, Josef; Wessels, Hendrik; von Richter, Oliver; Hornuss, Cyrill; Poetzl, Johann; Roth, Karsten (Frontiers in Immunology, 2024)
BackgroundBiosimilar natalizumab (biosim-NTZ) is the first biosimilar monoclonal antibody of reference natalizumab (ref-NTZ) for treatment of relapsing forms of multiple sclerosis (MS). Within the totality of evidence for demonstration of biosimilarity, immunogenicity assessments were performed in healthy subjects and patients with relapsing-remitting MS (RRMS) to confirm a matching immunogenicity profile between biosim-NTZ and ref-NTZ.MethodsImmunogenicity of biosim-NTZ versus ref-NTZ was evaluated in two pivotal clinical studies. In a comparative efficacy and safety study, patients with RRMS (n=264) received monthly infusions of biosim-NTZ/EU-ref-NTZ over 48 weeks. The primary endpoint period was Week 0 to Week 24. In a separate, comparative pharmacokinetic/pharmacodynamic (PK/PD) study, healthy subjects (n=450) received a single dose of biosim-NTZ, US-ref-NTZ or EU-ref-NTZ prior to an 85-day follow-up. In both studies, state-of-the-art, highly sensitive and drug tolerant bioanalytical assays were used to identify the proportion of participants with anti-drug antibodies (ADA) and neutralizing antibodies (NAb) against natalizumab over time.ResultsIn the comparative efficacy and safety study, biosim-NTZ and EU-ref-NTZ demonstrated similar incidences of overall ADA (79.4% vs 73.7%, respectively) and NAb (68.7% vs 66.2%, respectively) at Week 24. ADA titers over time were also concordant throughout the study period. Switching treatment from EU-ref-NTZ to biosim-NTZ had no impact on treatment-related ADA/NAb or clinical responses. Likewise, the single-dose PK/PD study reported matching overall incidence of ADA between treatment groups and matching ADA titer profiles over time.ConclusionThe immunogenicity profile of biosim-NTZ was confirmed to match that of ref-NTZ in healthy subjects and patients with RRMS by applying highly sensitive methods.